2022
DOI: 10.1177/00045632221128686
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals for clinical biochemistry and haematology tests during normal pregnancy

Abstract: Background Pregnancy induces physiological changes which affect biochemical and haematological parameters. As the significance of laboratory test results change throughout pregnancy, the reference interval (RI) or key result interpretive guide, should be specific to pregnancy. This study sought to establish trimester-specific-RIs for routine biochemical and haematological tests in healthy white European women with singleton pregnancies with comparison to RIs for non-pregnant European adults. Methods A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…We read with interest the article by Groenendijk et al, in which normative pregnancy-specific levels are reported for 41 routine haematological and biochemical tests. 1 We appreciated this well-executed reference study for its rigorous approach to investigating partitioning by gestational age. However, we have concerns about the use of body mass index (BMI) as an exclusion criterion.…”
Section: Dear Editormentioning
confidence: 99%
“…We read with interest the article by Groenendijk et al, in which normative pregnancy-specific levels are reported for 41 routine haematological and biochemical tests. 1 We appreciated this well-executed reference study for its rigorous approach to investigating partitioning by gestational age. However, we have concerns about the use of body mass index (BMI) as an exclusion criterion.…”
Section: Dear Editormentioning
confidence: 99%
“…There is much confusion in the letter from Dockree et al commenting on the reference intervals during normal pregnancy paper. 1,2 The values used in determining reference intervals are always selected from disease-free subjects. Adding people to these calculations with known characteristics that make a disease diagnosis likely is unwise and serves no legitimate clinical purpose.…”
mentioning
confidence: 99%